Digital camera based fingerprint recognition - Hiew, Bee Yan; Teoh, Andrew Ben Jin; Pang, Ying Han (2007)
Touch-less fingerprint recognition deserves increasing attention as it lets off the problems of deformation, maintenance, latent fingerprint problems and so on that still exist in the touch-based fingerprint technology. However, problems such as the low ridges-valleys contrast in the fingerprint images, defocus and motion blurriness raise when developing a digital camera based fingerprint recognition system. The system comprises of preprocessing, feature extraction and matching stages. The proposed preprocessing stage presents the promising results in terms of segmentation, enhancement and core point detection. Feature extraction is done by Gabor filter followed by Principle Component Analysis (PCA) and the favorable verification results are attained with Cosine Angle.